Blackness and the God of the Oppressed - Mdingi, Hlulani (The ecumenical review, 2022)
The state of blackness oscillates between two speculative positions: The first puts forward the irrelevance of race in the modern technological period, a view often coming from those who are colour blind and “optimistic” futurists. The second postulates the need to reaffirm the condition of blackness in a racist and capitalistic production-driven society. The article argues that in whatever direction technology is going, perhaps through its God complex, idolatry, and the enormous funding behind artificial intelligence, technology and so on, blackness in the age of technology is still an insignia toward humanization and liberation. The eschatological dystopia often portrayed in science fiction is, in fact, here and now; therefore, we must pause and ask if modern technology is a friend, a foe, or just a distraction leading us into the abyss of decay, hopelessness, and landlessness. Political blackness should continue guiding our steps and reality in a world that fails to acknowledge the depths of its racism.